Conditions for regulation of platform work on the example of international experiences - Spytek-Bandurska, Grażyna (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The article outlines the development of platform work and briefly characterizes this form of employment. Key legal regulations and court rulings in selected European countries are analyzed. The choice of France, Italy and Spain resulted from experiences in attempts to regulate the rights of employees providing services via online platforms. The aim was to show the practice that served as a basis for the debate on the future shape of the directive on improving working conditions. By listing the legal measures provided for in it to ensure the correct determination of the employment status of contractors, attention was drawn to their ambivalence. They carry both benefits and threats, which requires a prudent and well-considered implementation of EU regulations, especially the legal presumption.